A comparison of four methods for PCR inhibitor removal. (May 2015) - Hu, Qingqing; Liu, Yuxuan; Yi, Shaohua; Huang, Daixin
Highlights: The ability of four methods for the removal of PCR inhibitors was compared. The PowerClean ® kit was very effective for the removal of various inhibitors. The DNA IQ™ System was of similar ability with the PowerClean ® DNA kit. The ability of the Chelex ® -100 method to remove PCR inhibitors is the worst. Abstract: Biological samples collected from the crime scenes often contain some compounds that can inhibit the polymerase chain reaction (PCR). The removal of PCR inhibitors from the extracts prior to the PCR amplification is vital for successful forensic DNA typing. This paper aimed to evaluate the ability of four different methods (PowerClean ® DNA Clean-Up kit, DNA IQ™ System, Phenol–Chloroform extraction and Chelex ® -100 methods) to remove eight commonly encountered PCR inhibitors including: melanin, humic acid, collagen, bile salt, hematin, calcium ions, indigo and urea. Each of these PCR inhibitors was effectively removed by the PowerClean ® DNA Clean-Up kit and DNA IQ™ System as demonstrated by generating more complete short tandem repeat (STR) profiles from the cleaned up inhibitor samples than from the raw inhibitor samples. The Phenol–Chloroform extraction and Chelex ® -100 methods, however, could only remove some of eight PCR inhibitors. Our results demonstrated that the PowerClean ® DNA Clean-Up kit and DNA IQ™ System were very effective for the removal of known PCR inhibitors that are routinely found in DNA extracts from forensic samples.